On Properties of the Dual Quaternions (European Journal of Pure and Applied Mathematics, 2011)
In this paper, Euler’s and De Moivre’s formulas for complex numbers and quaternions are generalized for the dual quaternions. Also, the matrix representation of dual quaternions is expressed.